Clinical, radiological and surprise diagnosis of femoral hernia - Gandhi, Chinmay Sumatilal; Mote, Dajiram G. (International Surgery Journal, 2023)
The author has treated three cases of femoral hernias over the years. Femoral hernias are rare compared to inguinal hernias. Here, there were varied clinical presentations of all femoral hernias. Obstruction, strangulation and groin swelling were the presentations observed. Management of all varies according to presentation. Because of narrow neck and stiff femoral canal chances of complications are more. Use of minimal access techniques may reduce the morbidity of surgical treatment in emergency.